If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -5x + -6x = 7x Combine like terms: 9x + -5x = 4x 4x + -6x = 7x Combine like terms: 4x + -6x = -2x -2x = 7x Solving -2x = 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -2x + -7x = 7x + -7x Combine like terms: -2x + -7x = -9x -9x = 7x + -7x Combine like terms: 7x + -7x = 0 -9x = 0 Divide each side by '-9'. x = 0 Simplifying x = 0
| 9(3y-9)-(2y+7)= | | 7x+2(x-2)=9x+12 | | w+(5/2)w=7.5 | | 12-7x=2x+20 | | 11y^2+3=36 | | 3xy-6xyz=3 | | 156=(6w-9) | | 2z^2=30+7z | | 6ab-8bc=4bd | | 5u+2v= | | -9d^2=-405 | | 2xy-xz=4 | | 8*8=8 | | 11/4(5/3x-7/4) | | 8*8=111 | | 8*5=70 | | x/-3+12 | | 6u+v=18 | | (2+4)*5+10-18+7+5*(7+1)+4*0= | | 2t/3=4/9 | | 6c+3u=36 | | (3b-c-4)=2 | | 81x-8=1 | | 81x-=1 | | 4.6w+0.19=5539 | | 4x-y+8=2 | | 26=-3x+5 | | (4x-y+8)=2 | | 3x^4+8x^3-15x-40=0 | | 3(x+1)=y | | .018c=36 | | f(x)=(x^2+4x+4)-3 |